The United Kingdom Ambivalence on Preservation of British Virgin Islands Status Quo as Tax Havens 2016 - Syahla, Ratelia Nabila; Putranti, Ika Riswanti; Puspapertiwi, Sheiffi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
2016 was highlighted as the year of the biggest and scandalous tax havens report in all over the world: the Panama Papers. This report contributes into country initiation in tax contribution and tax evasion criminalization. It highlights and offers new concept of tax havens by providing the new definition in offshore utilization as a part of tax havens scheme. Hence this thesis focuses on UK and BVI (British Virgin Islands) relations on how they form mutual relations in tax havens network and give a detrimental effect toward tax contribution. United Kingdom and British Virgin Islands form an umbilical relations as overseas territory and part of their financial services, hence their presence as part of United Kingdom tax havens assesses as part of United Kingdom contrary and ambivalance. Therefore this research focuses on how hegemonic country preserved their relations with their former colony into one affiliation, and aims on how harmful London curbs their former colony as a part of their offshore nexus in tax havens.